A Practitioner’s Experience as Chief Compliance Officer: Ideal Versus Reality - Joel Maloff (The Pinnacle)
The Chief Compliance Officer (CCO) role within organizations continues to grow and evolve. As reported by Snell in an interview with the CCO of a major healthcare organization, compliance is a critical element of strategic directions and organizational objectives. Compliance must not be considered a roadblock but rather one of strategic collaboration and a valued resource for the organization. There is no definitive guidebook for CCOs, and the external demands for compliance continue to grow and evolve rapidly. For example, in 2023, a Memorandum on Establishing the Fight Against Corruption was issued by the White House. In 2022, the Department of Justice (DoJ) issued directives empowering CCOs regarding the assurance of compliance and maintaining a high level of compliance awareness. The DoJ also asserted that other executive leadership must be held accountable for compliance. Many states have implemented laws designed to protect consumers, including the California Consumer Protection Act, partially based on the General Data Protection Regulations (GDPR) applied in Europe. As the CCO of a mid-sized Unified Communications as a Service (UCaaS) provider, however, the most significant challenge was the application of best practices for compliance as indicated by research and scholarly efforts with the realities of funding, profitability, and acceptance of compliance as a strategic asset. This article reviews compliance opportunities and challenges through the lens of what succeeded, what failed, and the compromises required in the real world rather than a romantic version where everything follows a best practices model.